DIGITAL PR COMMUNICATION AND ETHICAL RESPONSIBILITY: CHALLENGES OF TRANSPARENCY, PRIVACY, AND PUBLIC TRUST IN THE ONLINE ENVIRONMENT (American Journal of Interdisciplinary Research and Development, 2025)
This article analyzes the ethical foundations of digital PR communication by examining transparency, privacy protection, and the maintenance of public trust in the online environment. As organizations increasingly rely on digital platforms, the boundaries of professional responsibility expand, requiring PR practitioners to ensure authenticity, protect user data, and prevent manipulative communication practices. The study highlights the role of transparent sponsorship disclosure, responsible data handling, algorithmic accountability, and inclusive messaging as core components of ethical digital PR.